(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The use of MSCT in the field of diagnostics of chronic diseases of the middle ear opens up broad prospects for medical practice.Particularly valuable is the ability to assess the condition of the eardrum using this method. MSCT is able to determine with high accuracy the presence and degree of damage to the eardrum, which is a key aspect in the process of diagnostics and subsequent treatment of chronic diseases of the middle ear